Effect of Abdominal Massage before In Vitro Fertilization Injection on Alleviating Pain among Infertile Women - Ja Ock Ku; Young Joo Park; Jeong Wook Kim; Eun Joung Jeon; Jeong Hee Jang; Young Hee Cho; Hwa Yeun Cho; Jum Mi Park; Seung Shin Lee (Korean Society of Women Health Nursing, 2016)
PURPOSE: The purpose of this study was to evaluate the effect of abdominal massage on alleviating pain caused by the injection of recombinant gonadotropin for In Vitro Fertilization (IVF) among infertile women. METHODS: This study employed a nonequivalent control group non-synchronized design. A total sample of 149 infertile women who never experienced in vitro fertilization was recruited at C fertility center. Seventy women were assigned into experimental group and 79 into controls. The experimental group had been informed to do abdominal massage prior to the injection and to record their subjective pain using visual analogue scale. The control group had been informed to record their subjective pain in the same way just after the injection. RESULTS: Compared to the pre-tested pain scores, the pain scores in experimental group were significantly reduced by 0.7 points, whereas the control group increased by 0.9 points (t=-4.55, p=.001). CONCLUSION: This study confirms that the use of abdominal massage prior to the injection is an effective way to alleviate pain on injection site. This massage may be a useful intervention for infertile women about pain alleviation.